2018
DOI: 10.12691/jpar-3-1-8
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Prescription: Practices of Healthcare Professionals in Hospital Setting, Kenya

Abstract: Physical inactivity is a serious epidemic that affects one's health and there's evidence that exercise can improve quality of life and health. The healthcare setting has been recognized as an appropriate and promising venue for counseling and prescribing physical activity to increase activity index of the population. An exercise prescription from a healthcare professional will remind the patient that physical activity is part of their treatment plan and should be adhered to with the same diligence with which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the first stage, stratified sampling was employed to select SMEs from the study population, while purposive sampling was employed to select one key respondent from each of the chosen SMEs at the second stage. The sample size for this study was calculated using the Yamane (1967) formula for sample size determination as cited in (Singh & Masuku, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In the first stage, stratified sampling was employed to select SMEs from the study population, while purposive sampling was employed to select one key respondent from each of the chosen SMEs at the second stage. The sample size for this study was calculated using the Yamane (1967) formula for sample size determination as cited in (Singh & Masuku, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…When all is said in done, the sample size utilized in an investigation is resolved dependent on the expense of information assortment, and dependent on adequate factual force. To work out the sample size of the study the formula suggested by Olutende et al [15] and Paudel et al [16] has been used. It suggests that n 0 = z 2 pq/e 2 Where, N 0 = sample size required for study, Standard tabulated for level of significance (z) = 1.96, p= prevalence or proportion of an event%= 0.50 [17].…”
Section: B Sample Size Determinationmentioning
confidence: 99%
“…The research sample was taken stratified randomly from all departments (operation room, hemodialysis room, emergency room, internist room, pulmonary room, surgery care room, medical checkup, and polyclinics). Determination of respondents using random sampling method (Singh & Masuku, 2014). All members of the nurse population are given a serial number, the serial number is written on small paper and rolled up, then inserted into a closed glass which is given a small hole, the researcher then shakes the glass, each number that comes out is made a respondent.…”
Section: Design Of Study and Participantsmentioning
confidence: 99%